APATITE-GROUP MINERALS FROM NEPHELINE SYENITE, PILANSBERG ALKALINE COMPLEX, SOUTH AFRICA - Liferovich R.P.; Mitchell R.H. (My University, 2006)
The nepheline syenites of the Pilansberg alkaline complex (South Africa) have undergone extensive subsolidus equilibration and alteration with a deuteric Cl- and Na-rich fluid phase. Complex assemblages of secondary minerals result from the replacement of primary aluminosilicates, rinkite, eudialyte and fluorapatite. The composition of apatite group minerals formed during these alteration processes reflects the Sr- and rare earth element (REE) content, Na/Cl ratio and pH of the deuteric fluids. Apatite-group minerals are observed to have formed in the following sequence: orthomagmatic fluorapatite; strontian britholite-(Ce); strontian fluorapatite; Sr-apatite; REE-rich Sr-apatite; Sr-Na-REE-rich minerals approaching the stoichiometry of belovite-(Ce) and deloneite-(Ce); britholite-(Ce). Increasing alkalinity of the deuteric fluids is reflected by increasing amounts of Sr replacing Ca in apatite and culminates in the formation of Sr apatite containing 62.1 wt.% SrO (~4.17 a.p.f.u. Sr). Pilansberg apatite-group minerals form a near-complete solid solution between fluorapatite and a fluorine analogue of Sr apatite with limited solution towards belovite-(Ce), Si-rich belovite-(Ce) and strontian britholite-(Ce). © 2006 The Mineralogical Society.
Keywords: ALTERATION; BELOVITE-(CE); BRITHOLITE-(CE); FOYAITE; HYPERAGPAITIC; LUJAVRITE; PILANSBERG; SR-APATITE; STRONTIAN; SUBSOLIDUS